METAPHORS IN BUGISNESE SONG LYRICS: SEMANTIC COGNITIVE STUDY - Haeran, Haeran (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2021)
The Bugisnese song lyrics use many methapors by their creators as expression forms of social reality. This study aims to describe the kinds of metaphors analyzed from the semantic cognitive aspect. The study is qualitative research. The study uses the semantic cognitive approach. Data sources are taken from Bugisnese song lyrics composed by Ancha Mahendra and Ansar S. from year 2000 to year 2010. Data collection procedures consist in reading and listening attentively then continued by note taking. After data collection, data are analyzed in the steps of data reduction, data presentation, and conclusion. The research results show that using of structural metaphors was more dominantly found in Bugisnese song lyrics than in orientational and ontology metaphors. Three kinds of metaphors are found; namely ten structural metaphors, one orientational metaphors, and four ontology metaphors. The use of structural metaphors is found more indicating that the song authors do not want to convey the lyrics purposes directly, but choose to transfer the purposes of song lyrics into concept of objects that have physical characteristics.Keywords: metaphor, song lyrics, Bugisnese song, semantic cognitiveMETAFORA DALAM LIRIK LAGU BUGIS: KAJIAN SEMANTIK KOGNITIFAbstrakLirik lagu Bugis banyak menggunakan metafora yang oleh penciptanya digunakan sebagai bentuk ekspresi penggambaran realitas sosial. Penelitian ini bertujuan untuk mendeskripsikan jenis metafora dalam lirik lagu Bugis yang dikaji dari segi semantic kognitif. Penelitian ini merupakan penelitian kualitatif. Pendekatan yang digunakan adalah pendekatan semantik kognitif. Sumber data diambil dari lirik lagu Bugis yang diciptakan oleh Ancha Mahendra dan Ansar S. dari tahun 2000—2010. Teknik pengumpulan data digunakan dengan teknik baca dan simak dilanjutkan dengan teknik catat. Setelah data terkumpul, kemudian dianalisis dengan beberapa tahap yakni berupa reduksi data, penyajian data kemudian penyimpulan. Hasil penelitian ini menunjukkan bahwa penggunaan metafora struktural lebih banyak digunakan dalam lirik lagu Bugis dari pada metafora orientasional dan ontologis. Ditemukan metafora yang terbagi menjadi tiga jenis, yaitu sepuluh metafora struktural, satu metafora orientasional, dan empat metafora ontologis. Penggunaan metafora struktural lebih banyak ditemukan karena mengisayaratkan bahwa pencipta lagu tidak ingin menyampaikan maksud lirik secara langsung, tetapi lebih memilih mentransferkan maksud lirik lagu ke dalam konsep benda yang memiliki sifat fisik.Kata Kunci: metafora, lirik lagu, Bugis, semantik kognitif